Sustainable everyday culture from glocal archipelago culture - Katriina Siivonen (Routledge, 2022)
The aim of the chapter is to problematize the idea of harmony between humanity and nature as an expression of ecological sustainability used, for instance, in cultural heritage activities. To better reach ecological sustainability, the relationship between humanity and nature needs to be uniformly redefined. We cannot stop the inevitable change of traditions and culture or the process of anthroposemiosis. The direction of cultural change is not necessarily towards a more ecologically sustainable world. There are tendencies towards the overuse of natural resources, even in areas where human beings have a strong commitment to nature, like in the Southwest Finland Archipelago. However, unlike outside human authorities, nature and the sea are perceived as strong controlling factors of the actions and identities of the people and are accepted as authorities with a power over those who live and move there. This can be a lesson to learn from this region that could assist us in achieving ecological and cultural sustainability. What we must do is guide cultural change, and apply the understanding that nature exerts power over human systems to all aspects of our future development.
Cultural Sustainability and the Nature-Culture Interface, Livalihoods, Policies, and Methodologies